Model Pemberdayaan UMKM Penggiat Wisata Lok Baintan Melalui Wakaf Temporer Jukung Berbasis Dana CSR - Rahmah Hayati; Ida Busnetty (At-Taradhi Jurnal Studi Ekonomi, 2026)
Tourism-based MSME empowerment in Lok Baintan, South Kalimantan, is constrained by limited capital, acute jukung shortages, unprofessional management, and consumptive CSR programs. This study develops and tests an integrative model: Temporary Jukung Waqf financed through CSR funds, treating corporate philanthropy as endowment capital (mawquf bih) for a temporary, depreciating movable-asset waqf.Employing an exploratory sequential mixed-methods design, qualitative data from 15 MSME actors mapped the problem structure, while a seven-member expert panel conducted Analytic Network Process (ANP) pairwise comparisons. The ANP results indicate that the Waqf Institution (Nazhir) is the highest-priority factor for success, followed by the Productive Business Facility (Jukung), CSR Fund Allocation, MSME Capacity, and Model Sustainability. Ultimately, this model reinforces sharia-based local economic strengthening and guides corporations to redirect CSR into productive waqf assets. Given the single-site scope, findings offer a context-specific priority structure; thus, multi-site replication and longitudinal economic-impact assessments are recommended.